What dominates most? The opinion of preservice biology teachers about factors associated with motivation to conduct innovative learning - Ahmad Kamal Sudrajat; Dita Purwinda Anggrella; Ahmad Iskak Nugroho (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
This article discusses the views of preservice biology teachers regarding the factors that dominate their motivation for innovative learning. A total of 152 preservice biology teachers were involved in this study. A correlation test was conducted to determine the relationship between curriculum design, school design, and class design with motivation to implement innovative learning. Data was collected using a questionnaire. The study results show that curriculum, school, and class design are collectively related to the motivation of preservice biology teachers to carry out innovative learning. Based on further analysis, the curriculum design factors significantly contributed to this relationship, while school and classroom design did not contribute significantly to this relationship. These results show that good curriculum design will support implementing innovative learning in the classroom. We recommend some things related to curriculum, school, and class design, the essence of which is the need to seek advice from students and teachers when renovating or building a school. Technology integration is also an important thing to include in the design plan. The government and related parties can use the results of this study in designing their schools or classrooms.Abstrak. Artikel ini membahas pandangan calon guru biologi mengenai faktor-faktor yang mendominasi motivasi mereka untuk pembelajaran inovatif. Sebanyak 152 calon guru biologi terlibat dalam penelitian ini. Data dikumpulkan menggunakan questionairre. Uji korelasi dilakukan untuk mengetahui hubungan antara curriculum design, school design, dan classroom design dengan motivasi untuk melaksanaan pembelajaran inovatif. Hasil penelitian menunjukkan bahwa desain kurikulum, sekolah, dan kelas secara kolektif berkaitan dengan motivasi guru biologi prajabatan untuk melaksanakan pembelajaran inovatif. Berdasarkan analisis lebih lanjut, faktor desain kurikulum berkontribusi signifikan terhadap hubungan ini, sementara desain sekolah dan kelas tidak berkontribusi signifikan terhadap hubungan ini. Hal ini menunjukkan bahwa desain kurikulum yang baik akan menunjang implementasi pembelajaran inovatif di kelas. Kami merekomendasikan beberapa hal yang berkaitan dengan kurikulum, sekolah, dan desain kelas, yang intinya adalah perlunya meminta saran dari siswa dan guru ketika merenovasi atau membangun sekolah. Integrasi teknologi juga merupakan hal yang penting untuk dimasukkan dalam rencana desain. Pemerintah dan pihak terkait dapat menggunakan hasil penelitian ini dalam merancang sekolah atau ruang kelasnya.